A Kink that Makes You Sick: The Incentive Effect of Sick Pay on Absence - Petri Böckerman; Ohto Kanninen; Ilpo Suoniemi (Institute for the Study of Labor (IZA), 2014)
This paper examines the effect of the replacement rule of the Finnish sickness insurance system on the duration of sickness absence. A pre-determined, piecewise linear policy rule in which the replacement rate is determined by past earnings allows identification of the effect using a regression kink design. We find a substantial and robust behavioral response. The statistically significant point estimate of the elasticity of the duration of sickness absence with respect to the replacement rate is on the order of 1.4.
Keywords: I13; I18; J22; 330; sick pay; labor supply; sickness absence; paid sick leave; regression kink design